The development of "kid's adventure with bawang putih & bawang merah interactive storybook" software using 2D approach / Norlida Mohamed - Mohamed, Norlida (2005)
In summary, the objective of this thesis is to clarify in details from all aspect in designing and developing edutainment software based on selected storybook using 2D Animation approach. With the multimedia technology, the impacts towards the user will be more effective compared to just reading a storybook. This software is specifically designed for children aging 6 to 9 years old. The story that covered in this software is Malay Folklore of "Bawang Putih & Bawang Merah". With the fusion of multimedia elements, boringness during reading book can be avoided. It also gives the user different kind of excitement and experience compare by reading the book alone. This project is being designed and developed using Macromedia Flash MX 2004. The Waterfall Model has been chose by the developer in order to accomplish this project successfully by delivering the goals that it intended to meets at the end of the phase. In order to get users feedback about this project, the final product has been tested by the user (children aging 6 to 9 years old), and twenty set of questionnaires were distributed to the parents of the users that has been involved during the testing phase of this project. Feedbacks returned by the respondents and findings that have obtained also being discussed by the developer in this thesis report.